Job Satisfaction Differences between Primary Health Care and Treatment Sectors: An Experience from Iran - Shokoufe Bagheri; Ali Janati; Ahmad Kousha; Homayoun Sadeghi-Bazargani; Mohammad Asghari-Jafarabadi; Mostafa Farahbakhsh (Tabriz University of Medical Sciences, 2013)
Background: The aim of this study was to compare the levels of job satis¬faction and its predictors among primary health care and treatment sectors' staff in East Azerbaijan Province, Iran.Methods: This comparative study was conducted in East Azerbaijan Province, Iran in 2011. A questionnaire survey was performed on 420 staff from health care and treatment sectors using multi-stage proportional cluster sampling method. Job satisfaction was measured in five aspects namely: structural and managerial; individual; social; work-itself; environ¬mental and welfare job satisfaction factors. The job satisfaction measure¬ment score was normalized to fall into a range of zero to 100. Statistical analyses were performed using Friedman and independent sample t-tests.Results: Overall satisfaction in health and treatment sectors was moderate with a mean score above 50. Hospital General Practitioners reported sig¬nifi¬cantly higher job satisfaction score (mean ± SD=57.34 ± 17.02) com¬pared to health care center General Practitioners (mean ± SD= 31.74±14.99). The highest satisfaction scores belonged to individual factors both in health care sector staff (64.83±18.50) and treatment sector staff (63.55±17.44). The lowest job satisfaction was observed with environmental and welfare factors (38.47±19.86 and 36.83±19.86, respectively).Conclusion: The job satisfaction significantly differs between primary health care and treatment sectors. Based on the results, environmental and welfare factors may be targeted to improve the job satisfaction in public health care system.